Investigating Propionibacterium acnes antibiotic susceptibility and response to bacteriophage in vitro and in vivo - Yu, Ruixing; Yu, Lingyun; Ning, Xiaoli; Cui, Yong (Frontiers in Microbiology, 2024)
A total of 94 Propionibacterium acnes (P. acne) isolates were obtained from a hospital in Beijing to evaluate their susceptibility to erythromycin, clarithromycin, doxycycline, and minocycline. As well as the determination of the effectiveness of P. acnes phages in vitro and in P. acnes-induced lesions mouse model. Patients with acne vulgaris (AV) were enrolled from August 2021 to October 2022. Standard methods were employed for specimen collection, culture, and identification of P. acnes.Susceptibility testing was conducted using E-strips for erythromycin, clarithromycin, minocycline, and doxycycline. Phage culture and identification followed standard procedures. A mouse model with P. acnes-induced skin lesions was established, and data was analyzed using χ2 test. The results showed that all isolates were susceptible to minocycline and doxycycline, while 53 (56.4%) and 52 (55.3%) isolates were susceptible to erythromycin and clarithromycin, respectively. Interestingly, younger patients and those with lower acne severity exhibited reduced resistance. Phage cleavage rates ranged from 88.30% to 93.60%. Multilocus sequence typing (MLST) analysis was conducted on 8 randomly selected P. acne isolates, and the IA-2 subtype was used in experiments to address P. acnes-induced lesions in mice. Phage therapy proved effective in this model. This study highlights the high susceptibility of P. acnes to doxycycline and tetracycline, while erythromycin and clarithromycin exhibited elevated resistance. Additionally, P. acnes phages demonstrated high cleavage rates and potential effectiveness in treating P. acnes-induced lesions. These findings suggest promising avenues for further exploration of phage therapy in acne treatment.